Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Motivasi Kerja Pegawai di Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Bone Bolango - Abdulrahman Pakaya; Abdulrahim Maruwae; Vera Pebriani Hasan (Journal on Education, 2022)
The research aimed to determine the effect of occupational safety and health on employees’ work motivation at the Regional Agency for Disaster Management (BPBD) of Bone Bolango Regency. It employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to employees of the Regional Agency for Disaster Management of Bone Bolango Regency. In the meantime, the research samples were 50 respondents, and the data analysis technique was done through simple linear regression. The research finding depicted that there was an effect of occupational safety and health on employees’ work motivation at the Regional Agency for Disaster Management (BPBD) of Bone Bolango Regency, with a percentage of 75.2%. In comparison, the remaining 24.8% were affected by other variabels that were not examined in this research.